Computerized continuous ECG monitoring during dental surgical procedures in local anesthesia - Illes, Davor (Array, 2001)
Development of technology enabled inexpensive and efficient continuous computerized electrocardiographic monitoring. Special ECG device for use in emergency purposes was constructed. Device was tested on patients who had dental surgical procedures in local anesthesia. Two cases of patients losing consciousness and heartbeat were recorded and analyzed. ECG proved to be useful for prevention of serious complications and in treatment control of emergencies in dentistry. Another significant usage is screening of general dental population in search of cardiovascular diseases.